2023
DOI: 10.2460/javma.22.08.0375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiologic features of SARS-CoV-2 in dogs and cats compiled through national surveillance in the United States

Abstract: OBJECTIVE To characterize clinical and epidemiologic features of SARS-CoV-2 in companion animals detected through both passive and active surveillance in the US. ANIMALS 204 companion animals (109 cats, 95 dogs) across 33 states with confirmed SARS-CoV-2 infections between March 2020 and December 2021. PROCEDURES Public health officials, animal health officials, and academic researchers investigating zoonotic SARS-CoV-2 transmission events reported clinical, laboratory, and epidemiologic information throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
4
11
1
Order By: Relevance
“…The animals were in contact with at least one person who tested positive for SARS-CoV-2. These results confirmed that dog owners are the most frequent sources of infection, as previously reported by others [ 37 ]. However, this is not the first report of dog infection in Mexico because SENASICA previously reported another case to the OMSA [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…The animals were in contact with at least one person who tested positive for SARS-CoV-2. These results confirmed that dog owners are the most frequent sources of infection, as previously reported by others [ 37 ]. However, this is not the first report of dog infection in Mexico because SENASICA previously reported another case to the OMSA [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Many of the seropositive animals identified by our serosurveillance [ 19 ] showed no clinical signs, mild clinical signs or had signs likely unrelated to SARS-CoV-2 infection at the time of sampling. This finding was consistent with numerous reports of mild or subclinical feline infections [ 2 , 3 , 4 , 5 , 9 , 11 , 20 , 21 , 22 , 23 ]. Additionally, seropositive animals might have experienced historical infections.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous experimental [ 2 , 3 , 4 , 5 , 20 ] and natural [ 11 , 21 , 22 ] infections of domestic cats have been reported as subclinical or very mild. However, one study reported that 50% (n = 55) of infected cats showed clinical signs, with sneezing and lethargy being the most noted [ 23 ], and another reported respiratory and/or gastrointestinal signs in four of twelve cats infected with the Delta variant [ 24 ]. Additionally, a cat became severely ill when infected with SARS-CoV-2 in 2020, showing mainly respiratory signs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding a biological perspective, a more robust immune response to SARS-CoV-2 was demonstrated to be present in cats compared to dogs, and the risk of infection in pets is associated with the burden of human disease in their environment [ 54 ]. In addition, in America and Europe, cats and dogs respond differently to SARS-CoV-2 on their immune systems [ 31 , 55 ]. Compared to dogs, cats have demonstrated a greater seroprevalence and higher titers of neutralizing antibodies, suggesting a stronger immunological response [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in America and Europe, cats and dogs respond differently to SARS-CoV-2 on their immune systems [ 31 , 55 ]. Compared to dogs, cats have demonstrated a greater seroprevalence and higher titers of neutralizing antibodies, suggesting a stronger immunological response [ 55 ]. Dogs, on the other hand, had a milder course of infection than cats because they showed differences in the results of the ELISA and serum neutralization test, which may have been caused by cross-reactions with other animal coronaviruses [ 56 ].…”
Section: Discussionmentioning
confidence: 99%